Association of STAT3 and STAT4 polymorphisms with susceptibility to chronic hepatitis B virus infection and risk of hepatocellular carcinoma: a meta-analysis. Issue 6 (20th June 2019) - Shi, Han; He, Hongyan; Ojha, Suvash Chandra; Sun, Changfeng; Fu, Juan; Yan, Mao; Deng, Cunliang; Sheng, Yunjian
Abstract : Background: It has been reported that polymorphisms of signal transducer and activator of transcription (STAT ) 3 and STAT4 might be associated with susceptibility to hepatitis B virus (HBV) infection and risk of chronic hepatocellular carcinoma (HCC). Owing to limitation of sample size and inconclusive results, we conducted a meta-analysis to clarify the association.Methods: We identified relevant studies by a systematic search of Medline/PubMed, Embase, Web of Science and the Cochrane Library up to 20 February 2019. The strength of the association measured by odds ratios (OR) with 95% confidence intervals (CIs) was studied. All the statistical analyses were conducted based on Review Manager 5.3 software.Results: A total of 5242 cases and 2717 controls from five studies were included for the STAT3 polymorphism, 5902 cases and 7867 controls from nine studies for the STAT4 polymorphism. Our results suggested that STAT3 rs1053004 polymorphism was a significant risk factor of chronic HBV infection (C vs. T: OR = 1.17, 95% CI: 1.07–1.29, P A =0.0007; CC + CT vs. TT: OR = 1.38, 95% CI: 1.09–1.76, P A =0.008). Validation with all the genetic models revealed that rs7574865 polymorphism of STAT4 gene was closely associated with chronic HBV infection ( P A <0.01) and chronic hepatitis B (CHB)-related HCC ( P A <0.05). Meanwhile, the authenticity of the above meta-analysis results was confirmed by trial sequential analysis (TSA).Conclusions: The meta-analysis showed that STAT3 rs1053004 polymorphism may be the risk for developing chronic HBV infection but not associated with HCC. The present study also indicates that STAT4 rs7574865 polymorphism increased the risk of chronic HBV infection and HCC.